Understanding and perceptions of final-year Doctor of Pharmacy students about generic medicines in Karachi, Pakistan: a quantitative insight - Jamshed, Shazia Qasim; Ibrahim, Mohamad Izham Mohamad; Hassali, Mohamad Azmi; Sharrad, Adheed Khalid; Shafie, Asrul Akmal; Babar, Zaheer-Ud-Din (Dovepress Medical Press, 2015)
General objective: To evaluate the understanding and perceptions of generic medicines among final-year Doctor of Pharmacy students in Karachi, Pakistan. Methods: A 23-item survey instrument that included a question on the bioequivalence limits and Likert-type scale questions regarding the understanding and perceptions of generic medicines among the students was executed. Cronbach’s alpha was found to be 0.62. Results: Responses were obtained from 236 final-year Doctor of Pharmacy students (n=85 from a publicly funded institute; n=151 from a privately funded institute). When comparing a brand-name medicine to a generic medicine, pharmacy students scored poorly on bioequivalence limits. More than 80% of the students incorrectly answered that all the products that are rated as generic equivalents are therapeutically equivalent to each other (P,0.04). Half of the students agreed that a generic medicine is bioequivalent to the brand-name medicine (P,0.001). With regard to quality, effectiveness, and safety, more than 75% of the students disagreed that generic medicines are of inferior quality and are less effective than brand-name medicines (P,0.001). More than 50% of the students disagreed that generic medicines produce more side effects than brand-name medicines (P,0.001). Conclusion: The current study identified a positive perception toward generic medicines but also gaps in the understanding of generic medicines. Pharmacy students lacked a thorough understanding of the concepts of bioequivalence. Pharmacy academia should address these issues, which will help build confidence in generic medicines and increase the generic medicine